Regulation and third-party discrimination in vertically related markets: The case of German electricity - Gert Brunekreeft (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2001)
This paper explores the relation between the regulation of monopolistic upstream prices and the incentives of a vertically integrated input monopolist to discriminate third parties on the downstream market. Currently, this is an issue in network industries like telecommunications, electricity and railways and has sparked off a controversy in the literature. The paper examines how the incentives to discriminate depend on the level of the upstream prices, the potential competitiveness of the downstream market and the efficiency of the competitors as compared to the integrated firm's downstream subsidiary. The insights are applied to the electricity supply industry in Germany.
Keywords: L42; L51; L94; 330; regulation; discrimination; vertical integration; electricity; Elektrizitätswirtschaft; Energieverbund; Netzzugang; Preisdifferenzierung; Elektrizitätspolitik; Theorie; Deutschland